2020
DOI: 10.1186/s12887-020-1974-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of the adenosine triphosphate sensitivity assay in infantile vascular anomalies

Abstract: Background: The term vascular anomalies include various vascular tumors and vascular malformations, among them infantile hemangiomas and capillary malformations are the most well-known associated diseases in early ages. Multiple drugs have been introduced for intervention, but susceptibility test in vitro were scarcely reported. Objective: To evaluate the inhibition effect of different drugs by adenosine triphosphate sensitivity assay in vitro before the treatment of infantile hemangiomas and capillary malform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Itraconazole prevented lung cancer endothelial cells from proliferating and migrating; moreover, it exhibited an antiangiogenic effect via the inhibition of tube formation [ 16 ]. Itraconazole has been proven to be a potential therapeutic for IH in various studies [ 6 , 7 , 11 , 17 ]. Another study reported that itraconazole promoted the regression of IH through the inhibition of platelet-derived growth factor (PDGF) [ 18 ]; however, this finding can only partly explain the inhibitory effect of itraconazole on IH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Itraconazole prevented lung cancer endothelial cells from proliferating and migrating; moreover, it exhibited an antiangiogenic effect via the inhibition of tube formation [ 16 ]. Itraconazole has been proven to be a potential therapeutic for IH in various studies [ 6 , 7 , 11 , 17 ]. Another study reported that itraconazole promoted the regression of IH through the inhibition of platelet-derived growth factor (PDGF) [ 18 ]; however, this finding can only partly explain the inhibitory effect of itraconazole on IH.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians found that itraconazole promoted hemangioma regression when used for the treatment of fungal infection of IH [ 6 ]. In addition, itraconazole exerted a significant inhibitory effect on IH cells in vitro [ 7 ]. Furthermore, this drug inhibits endothelial cell proliferation and tube formation by blocking the signaling pathway related to vascular endothelial growth factor receptor 2 (VEGFR2) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The liver function and blood test were normal during the treatment, and conditions continued to improve 6 mo after withdrawal of the medicine. Moreover, Li et al [ 13 ] selected specimens of 5 IHs cases and 11 capillary malformations to perform an adenosine triphosphate sensitivity assay to detect the growth inhibition activity of propranolol, rapamycin, sildenafil, and itraconazole[ 13 ]. They found that itraconazole exhibited clear inhibition on the cellular proliferation of both IHs and capillary malformations[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Li et al [ 13 ] selected specimens of 5 IHs cases and 11 capillary malformations to perform an adenosine triphosphate sensitivity assay to detect the growth inhibition activity of propranolol, rapamycin, sildenafil, and itraconazole[ 13 ]. They found that itraconazole exhibited clear inhibition on the cellular proliferation of both IHs and capillary malformations[ 13 ]. Bessar et al [ 14 ] investigated the efficacy of propranolol and itraconazole on IHs by observing the variation of serum angiopoietin-2.…”
Section: Discussionmentioning
confidence: 99%